THE EFFECT OF PICLORAM AND LIGHT ON SOMATIC EMBRYOGENESIS REGENERATION OF PINEAPPLE - Roostika, Ika; Khumaida, Nurul; Mariska, Ika; Wattimena, Gustaaf Adolf (Indonesian Agency for Agricultural Research and Development - MOA, 2012)
Smooth Cayenne is the largest pineapple type cultivated in Indonesia, but its vegetative planting materials for mass propagation are limited. Somatic embryogenesis is a potential method to be applied. The aim of this study was to investigate the somatic embryogenesis regeneration under the effect of picloram and light. Callus formation was induced by picloram (21, 41 and 62 μM) added with 9 μM thidiazuron. The calli were transferred onto MS or Bac medium enriched with N-organic compounds with or without addition of 21 μM picloram under dark or light condition. The compact calli were subcultured onto MS medium supplemented with 4.65 μM kinetin, while the friable calli were transferred onto BIG medium (modified MS + 1.1 μM benzyl adenine + 0.9 μM indole butyric acid + 0.09 μM giberelic acid) or B medium (MS + 0.018 mM benzyl adenine). The results showed that the events of somatic embryogenesis were started from cell polarization, asymmetrical division, proembryo formation as embryogenic tissues and friable embryogenic tissues, and embryo development. The best treatment for callus induction was 21 μM picloram. The addition of 21 μM picloram on N-organic enriched medium and the use of light condition proliferated embryogenic calli. The N-organic enriched Bac medium and light condition yielded the highest number of mature somatic embryos (17 embryos perexplant in 2 months). The B medium was better than BIG medium to develop somatic embryos from friable embryogenic tissues. The somatic embryogenesis method presented is potential for pineapple mass propagation and artificial seedproduction.Abstrak Bahasa IndonesiaSmooth Cayenne merupakan kultivar nenas yang banyak dibudidayakan di Indonesia, namun ketersediaan benih untuk perbanyakan massal masih terbatas. Embriogenesis somatikadalah metode yang potensial untuk produksi bibit secara massal. Tujuan penelitian adalah untuk mempelajari pengaruh pikloram dan pencahayaan terhadap regenerasi embriogenesis somatik nenas. Kalus diinduksi menggunakan pikloram (21, 41, dan 62 μM) dan penambahan thidiazuron 9 μM. Selanjutnya, kalus dipindahkan ke media MS atau Bac yang diperkaya dengansenyawa N-organik dengan atau tanpa penambahan pikloram 21 μM dalam kondisi gelap atau dengan pencahayaan. Kalus kompak disubkultur pada media MS yang mengandung kinetin 4,65 μM, sedangkan kalus remah dipindahkan ke media BIG (MS modifikasi + bensil adenin 1.1 μM + indole butyric acid 0,9 μM + giberelic acid 0,09 μM) atau media B (MS + bensil adenin 0,018 μM). Hasil penelitian menunjukkan bahwa tahapan embriogenesis somatik diawali dengan polarisasi sel, pembelahan asimetris, pembentukan proembrio sebagai jaringan embriogenik danjaringan embriogenik remah, serta perkembangan embrio. Perlakuan terbaik untuk induksi kalus adalah pikloram 21 μM. Penambahan pikloram 21 μM pada media yang diperkaya dengan senyawa N-organik mampu meningkatkan jumlah kalusembriogenik. Media Bac yang diperkaya senyawa N-organik dan kondisi pencahayaan menghasilkan jumlah embrio somatik dewasa terbanyak (17 embrio per eksplan dalam 2 bulan). Media B lebih baik daripada media BIG untuk regenerasi embrio somatik dari jaringan embriogenik remah. Metode embriogenesis somatik yang dihasilkan dari penelitian ini berpotensi diterapkan untukperbanyakan massal dan produksi benih nenas.